Post-Asean Agreement on Transboundary Haze Pollution: How to Settle the Dispute Settlement? - Fadia Fitriyanti; Yordan Gunawan (Hasanuddin Law Review, 2019)
Forest fire happened several times in Indonesia which impacting neighboring countries, such as Malaysia and Singapore. ASEAN tried to "heal" and prevent the possibility of similar events by signing the ASEAN Agreement on Transboundary Haze Pollution (AATHP) for its members. In line with that, this research examined the concern of the state responsibility principle and its dispute resolution as well as a mechanism under the Agreement in dealing with the transboundary haze pollution in ASEAN. The research conducted by using normative theory by using primary, secondary and tertiary legal materials, collected from library research. Data analysis uses statute approach and case approach. Furthermore, the resulting research is in the form of analytical descriptive. The researchers argue that AATHP it is not explained in detail about the forms, mechanisms, and consequences that can be given to a country that has caused forest fires in the national jurisdiction and proven damage other countries. The researchers conclude that there should be a clear definition of state responsibility by means of a visible dispute settlement. Those mentioned steps are aimed to prepare for both preventive and punitive legal action for all members of ASEAN in dealing with the case of transboundary haze pollution.